Pertanggungjawaban Debitur Terhadap Kreditur Pada Perjanjian Kredit Dengan Jaminan Fidusia - Rizka Astri Husen; Nancy Silvana Haliwela; Agustina Balik (Faculty of Law Universitas Pattimura, 2023)
ABSTRACT: An agreement is an agreement made by one party and another party based on trust. It is the same with credit agreements with fiduciary guarantees that occur between debtors, creditors and third parties. Where a third party defaults, against the creditor. by not paying car loan installments. So that it results in a credit agreement between the Debtor and the Creditor. So that the action refers to the provisions of the Civil Code Article 1238, namely